Psychosocial changes following transition to an aged care home: qualitative findings from Iran. (6th October 2016) - Zamanzadeh, Vahid; Rahmani, Azad; Pakpour, Vahid; Chenoweth, Lynnette Lorraine; Mohammadi, Eesa
Abstract : Aims and objectives: The study explored the psychosocial effects of transitioning from home to an aged care home for older Iranian people. Background: Moving from one's own home to a communal aged care home is challenging for older people and may give rise to numerous psychosocial responses. The extent and intensity of such changes have rarely been explored in Middle Eastern countries. Design: Data were collected through purposive sampling by in‐depth semi‐structured interviews with 20 participants (17 people living in aged care homes and three formal caregivers). All the interviews were recorded and typed, and conventional qualitative content analysis was used, eliciting common themes. Results: There were four common themes: communication isolation, resource change, monotone institutional life and negative emotional response. Participants lost their previous support systems when transitioning to an aged care home and were not able to establish new ones. Routine care was provided by formal caregivers with little attention to individual needs, and minimal support was given to help maintain the older person's independence. These losses gave rise to negative emotions in some of the participants, depending on their previous lifestyle and accommodation arrangements. Conclusions: The extent and intensity of psychosocial changes occurring in most of the participants following their transition to an aged care home indicates the need for a review of Iranian aged care services. Implications for practice: To assist older Iranian people adapt more readily when making the transition to aged care home and to meet their unique psychosocial needs, a family‐centred approach to service delivery is recommended.